STUDENTS’ PERCEPTIONS ON THE USE OF MIND VECTOR APPLICATION FOR SPEAKING SKILL IN ENGLISH CLUB - Imam Hidayatullah Al Qadrie; Yohanes Gatot Sutapa Yuliana; Urai Salam (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
ABSTRACT The purpose of this research was to find out students’ perception about Mind vector application for arranging ideas at SMP 14 Pontianak who have joined English Club in academic year 2019/2020. This research applied descriptive research as form of research. This research focused on students’ perception that learners replied a questionnaire through Google Form. The participants were who have joined English Club. Based on the result showed there were two members of English Club that have already responded the questionnaire through Google Form. There were 20 items that students’ have chosen the questionnaire according to their perceptions about Mind Vector application. In the process of it, there was 1 student used Mind Vector many times in a day and another student used Mind Vector several times in a week the questionnaire had responded from two students that had different perception 1 student disagreed with Easy to access and arrange idea and Mind Vector application is my first choice in active of managing idea and thinking about the connection each idea that I have made on the application overall, 2 students had agreed with statement items that meant pupils at SMP N 14 who have joined contented about mind mapping, in different circumstance students Mind Vector application could be assisted them in managing ideas on that application Keywords: Mind Vector, Students’ Perception, Speaking Skill